The impact of mentoring quality on protégés' organization‐based self‐esteem and proactive behavior: The moderating role of traditionality - Wu, Xiangfan; Lyu, Yijing; Kwan, Ho Kwong; Zhai, Haiyan (Human Resource Management, 2019)
AbstractBased on self‐consistency theory, this study examined the relationship between mentoring quality as perceived by protégés and protégés' proactive behavior. It focused on the mediating role of organization‐based self‐esteem (OBSE) and the moderating role of traditionality. To examine these relationships, we administrated three‐wave surveys to 237 subordinate–supervisor dyads in a construction enterprise. The results of hierarchical linear modeling demonstrated that (a) mentoring quality and proactive behavior had a positive relationship; (b) OBSE mediated this relationship; and (c) traditionality strengthened both the relationship between mentoring quality and OBSE and the indirect effect of mentoring quality on proactive behavior via OBSE. Our findings have theoretical and practical implications for research on mentoring and proactive behavior.